Black Women’s Oppression in The Personal Librarian by Marie Benedict and Victoria Christopher Murray: A Matrix of Domination Analysis - Cahaya Ria; Robby Satria Mandala (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines how race, gender, and power shape the life of Belle da Costa Greene in the novel The Personal Librarian. This research uses a qualitative approach with close reading to analyze Belle, a Black woman who must hide her racial identity in a society dominated by white and patriarchal values. The study applies Patricia Hill Collins’s Matrix of Domination as the main theory, supported by Kimberle Crenshaw’s intersectionality. The analysis focuses on four domains of power: structural, disciplinary, hegemonic, and interpersonal. The findings show that Belle does not always face clear or direct discrimination. Instead, she experiences control in subtle ways. She must follow strict social expectations and carefully manage her behavior to hide her racial identity. She is also constantly watched in her workplace, which creates unequal power relations. The study explains that Belle’s struggles are not only personal, but are shaped by wider systems of racism and patriarchy. Overall, this research shows how racism and patriarchy work together to shape Belle’s experiences in The Personal Librarian. This study shows how oppression is represented through intersecting systems of power in the novel.